2003
DOI: 10.1177/120347540300700202
|View full text |Cite
|
Sign up to set email alerts
|

Skin Cancer Induced by Arsenic in the Water

Abstract: This study allows us to conclude that the relationship between arsenic and cancer is frequent and it describes the principal characteristics of this entity in our group of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 19 publications
0
28
0
1
Order By: Relevance
“…1). The characteristics of the included studies are described in Table 1 (Gerstenfeld et al, 2012;Carballo et al, 2006;Aballay et al, 2012;Ameer et al, 2014;Auge, 2014;Bartolotta et al, 2011;Blanco et al, 2012;Bobillo et al, 2014;Bonafina and Ratto, 2009;Cabrera and Gomez, 2003a;Campaña et al, 2014;Concha et al, 2006;Corey et al, 2005;Engstrom et al, 2009Engstrom et al, , 2011Escalante et al, 2009;Esposito et al, 2011;Ferral et al, 2014;Gonzalez Uriarte et al, 2002;Guber et al, 2009;Heredia and Fernandez, 2009;Hick and Carballo, 2005;Matos et al, 2000;Medina et al, 2004;Molina et al, 2014;Moschione et al, 2014;Navoni et al, 2006Navoni et al, , 2012Olivera et al, 2006;Olmos et al, 2014;Paoloni et al, 2005Paoloni et al, , 2009Peluso et al, 2011Peluso et al, , 2012Pou et al, 2011;Rigacci et al, 2013;Roman et al, 2014;Rosso et al, 2011Rosso et al, , 2013Sch...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1). The characteristics of the included studies are described in Table 1 (Gerstenfeld et al, 2012;Carballo et al, 2006;Aballay et al, 2012;Ameer et al, 2014;Auge, 2014;Bartolotta et al, 2011;Blanco et al, 2012;Bobillo et al, 2014;Bonafina and Ratto, 2009;Cabrera and Gomez, 2003a;Campaña et al, 2014;Concha et al, 2006;Corey et al, 2005;Engstrom et al, 2009Engstrom et al, , 2011Escalante et al, 2009;Esposito et al, 2011;Ferral et al, 2014;Gonzalez Uriarte et al, 2002;Guber et al, 2009;Heredia and Fernandez, 2009;Hick and Carballo, 2005;Matos et al, 2000;Medina et al, 2004;Molina et al, 2014;Moschione et al, 2014;Navoni et al, 2006Navoni et al, , 2012Olivera et al, 2006;Olmos et al, 2014;Paoloni et al, 2005Paoloni et al, , 2009Peluso et al, 2011Peluso et al, , 2012Pou et al, 2011;Rigacci et al, 2013;Roman et al, 2014;Rosso et al, 2011Rosso et al, , 2013Sch...…”
Section: Resultsmentioning
confidence: 99%
“…One study described the high prevalence of skin cancer in 23 patients with chronic arsenic poisoning who attended a hospital in the province of Buenos Aires (Cabrera and Gomez, 2003b). Another study in Tucuman showed the prevalence of HACRE in subjects consuming drinking water with As levels that exceeded the threshold of 10 and 50 μg/L (Gerstenfeld et al, 2012).…”
Section: Arsenic Associated To Skin Pathologiesmentioning
confidence: 95%
“…Bladder cancer mortality associated with arsenic in drinking water was reported in Córdoba, central Argentina (Hopenhayn-Rich et al 1996). Other studies concerned skin cancer (Cabrera and Gómez 2003) and bladder cancer in relation to direct arsenic exposure (Bates et al 2004). In addition, high fluoride concentrations in these waters are associated with dental fluorosis and sometimes bone fluorosis (de la Sota et al 1997).…”
Section: Introductionmentioning
confidence: 96%
“…The chronic and carcinogenic manifestations of ingesting As-contaminated groundwater for drinking purposes are of great concern to many researchers and health care workers, and international epidemiological, geochemical and medical-geochemical studies have focused on the problems associated with As-contaminated groundwater (e.g., Ahmed et al, 2004;Cabrera & Gó mez, 2003;Fletcher et al, 2003;Guo & Tseng, 2000;Tollestrup et al, 2005;Van Geen et al, 2002). The main aim of these studies has been the qualitative/quantitative health risk assessment related to increased levels of As in the environment in order to implement the appropriate mechanisms for minimalizing these levels.…”
Section: Introductionmentioning
confidence: 99%